Simulation Analysis of Cluster Effect of High-Shear Low-Pressure Grinding with Flexible Abrasive Tools - Chengjin Tian; Jinguo Han; Yebing Tian; Bing Liu; Zhiqiang Gu; Xintao Hu (Micromachines, 2021)
Based on the clustering effect of shear-thickening fluids (STFs), a high-shear low-pressure flexible grinding wheel has been developed. In order to explore the material removal mechanism, the coupled Eulerian—Lagrangian (CEL) method is adopted to simulate the novel grinding process. The simulation results show that particle clustering effects do occur at the tangential and bottom positions of the micro-convex peak when it instantaneously strikes the workpiece surface. The particle clusters drive the harder abrasive particles to resist the strong interactions of micro-convex peaks. The micro-convex peaks are removed due to the cutting effect of the harder abrasive particles. Compared with traditional grinding, the ratio of tangential force to normal force for the high-shear low-pressure flexible grinding wheel is improved. The various trends in force ratio are consistent with the experimental results, which verifies the effectiveness of high-shear low-pressure grinding.